An analysis of inhibitory functioning in individuals with chronic posttraumatic stress disorder. (January 2016) - Echiverri-Cohen, Aileen M.; Zoellner, Lori A.; Ho, William; Husain, Jawad
Highlights: Inhibitory deficits such as seen in prepulse inhibition and attentional blink may underlie cognitive abnormalities in PTSD. Deficits in prepulse inhibition were more prevalent in trauma-exposed individuals with PTSD compared to those without PTSD and healthy controls. Deficits in attentional blink were more prevalent in both trauma-exposed with and without PTSD compared to healthy controls. Prepulse inhibition and attentional blink were not strongly associated. These findings suggest a general faulty inhibitory mechanism associated with trauma exposure and PTSD. Abstract: Cognitive abnormalities in posttraumatic stress disorder (PTSD) may be a function of underlying inhibitory deficits. Prepulse inhibition (PPI) and attentional blink (AB) are paradigms thought to assess inhibition. Using a sample of 28 individuals with PTSD compared to 20 trauma-exposed and 19 healthy individuals, PPI was examined using white noise that was preceded by a tone, and AB was examined using a presentation of letters in a stream of numbers. Relative to the control group, the PTSD and trauma-exposed groups did not follow the u-shaped pattern in AB, suggesting trauma-exposure and subsequent PTSD are associated with similar impairment in attention. Individuals with PTSD showed reduced PPI compared to trauma-exposed and healthy individuals, suggesting individuals with PTSD exhibit faulty automatic processing. For individuals with PTSD, PTSD severity was associated with a decline in PPI. These findings suggest a general faulty inhibitory mechanism associated with trauma exposure and PTSD.